The Influence of Competence and Work Ethic on Teachers' Career Development at SMK Pelita Ciampea 2 - Siti; Istirhamiyah (Dinasti Publisher, 2025)
This study aims to analyze the influence of competence and work ethic on teachers' career development at SMK Pelita Ciampea 2. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 50 teachers. Data analysis uses the Partial Least Squares-Structural Equation Modeling (PLS-SEM) model. The results show that competence and work ethic have a positive and significant impact on teachers' career development. Good competence enhances professionalism, while a strong work ethic drives motivation and dedication in teaching. The implication of this study is the importance of schools improving teacher training and creating a supportive work environment to encourage career development.